Penerapan Media Cerita Hero Game Online Mobile Legend Untuk Meningkatkan Keterampilan Menulis Teks Tanggapan Siswa Kelas VII-I SMPN 4 Madiun - Imam Jihadi Muslim; Eni Winarsih; Sri Andayani (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research was motivated by the students' perceived low ability in learning to write response texts. The purpose of this research is to improve student learning outcomes in learning to write response texts to fiction reading. Actions were taken by implementing the mobile legend online game hero story text media in learning to write response texts for fiction reading. This research used a Class Action Research (PTK) design which was carried out over 2 cycles. The subjects in this research were students in class VII-I of SMPN 4 Madiun for the 2023-2024 academic year with a total of 32 students, consisting of 16 male students and 16 female students. The data in the research were taken through response text writing skills tests and learning observations. The data obtained was then analyzed using comparative descriptive analysis techniques. The research results showed that the ability to write response texts to fiction reading increased. This is proven by the increase in student learning outcomes from the pre-cycle stage to the second cycle stage. The percentage of students' learning completeness increased successively, namely 33%; 56%; and 83%. The average score obtained by students also increases with each lesson. The average increase in students' grades sequentially in each cycle is 51.25; 65.3; and 80.7